Nominee Arrangement Practices Performed by The Government of The Republic of Indonesia - Andy Putra Kusuma (Jurnal Hukum Volkgeist, 2022)
This study aims to analyze the synchronization of the Law on the Prohibition of Nominee Practices and Nominee Arrangements carried out by the Government of the Republic of Indonesia. This type of research is a normative juridical research by examining and synchronizing data sourced from legal principles and regulations as well as court decisions. The method of data collection is done by studying literature such as regulations, books, documents or other writings that support this research. The collected data was then analyzed qualitatively and comprehensively using data analysis methods. Based on the results of this study, it can be concluded that the application of the law to the parties who practice nominee has not been implemented optimally and thoroughly. As a form of Government attention to investment activities, the Government of the Republic of Indonesia has been explicitly regulated in Law Number 40 of 2007 concerning Limited Liability Companies (UUPT) and Law Number 25 of 2007 concerning Investment (UUPM) regarding the prohibition of nominee practices in any form. And the legal consequences of the nominee's practice are null and void. However, in its implementation.